Strategi Logika Untuk Sukses Dalam Penyelesaian Masalah (Berita Palsu/Hoax) Secara Efektif di Zaman Teknologi - Wita Marheni; Patricia Wira Lestari; Moses Lawalawata (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Logic is a branch of philosophy that discusses the rules, principles, laws and methods or procedures in achieving knowledge rationally and correctly, it is also a way to gain knowledge by using reason, words and language that is done systematically. Logic can be systematized into several groups depending on which perspective we see it from, seen from its quality logic can be divided into two namely naturalist logic (natural logic) and artificialist logic (scientific logic). Reasoning is a thought process in drawing a conclusion in the form of knowledge. Humans are essentially beings who think, feel, behave, and act. His attitudes and actions are based on knowledge gained through feeling or thinking activities. Reasoning produces knowledge that is associated with thinking activities. Reasoning is a thought process in drawing a conclusion in the form of knowledge. So reasoning is one or a process in thinking that combines two or more thoughts to draw a conclusion to get new knowledge. Nowadays, understanding and knowledge of logic, reasoning, and argumentation are increasingly needed not only for academics but also for members of society who deal with problems, especially technology, every day. Most of Indonesia is vulnerable to the spread of hate speech and fake news in cyberspace. This fake news often contains elements of hate speech against certain groups, such as ethnicity, religion, race, or class (referred to as SARA), which can trigger division and conflict in society.